[quotation] On livelihoods - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
On livelihoods: 'The area that people can exploit with shifting cultivation is getting smaller and smaller, and they are being put in a hopeless situation. Their traditional sustainable way of exploiting the forest is not sustainable anymore'....